Uprooted : How Breslau Became Wroclaw during the Century of Expulsions - Thum, Gregor, 1967- (Book collections on Project MUSE., 2011)
With the stroke of a pen at the Potsdam Conference following the Allied victory in 1945, Breslau, the largest German city east of Berlin, became the Polish city of Wroclaw. Its more than six hundred thousand inhabitants--almost all of them ethnic Germans--were expelled and replaced by Polish settlers from all parts of prewar Poland. Uprooted examines the long-term psychological and cultural consequences of forced migration in twentieth-century Europe through the experiences of Wroclaw's Polish inhabitants. In this pioneering work, Gregor Thum tells the story of how the city's new Polish settlers found themselves in a place that was not only unfamiliar to them but outright repellent given Wroclaw's Prussian-German appearance and the enormous scope of wartime destruction.